RAPTORS AND THEIR IMPORTANCE IN NATURE CONSERVATION - Umidjon Turdiyevich Murtazayev; Murod Rustamovich Turopov (Modern American Journals, 2025)
This article comprehensively examines the role of raptors in the ecological system, their significance in preserving biodiversity, and their contribution to nature conservation. It analyzes the main threats facing raptors and highlights global and regional measures being undertaken for their protection. The study demonstrates the crucial importance of raptors as key indicators for maintaining ecological stability.
Keywords: Raptors, Bird conservation, Ecology of raptors, Biodiversity, Ecosystem stability, Predatory birds, Food chain regulation, Population control, Bioindicators, Threatened species, Pesticides, Illegal hunting,Poaching, Power line collisions, Wind turbines